PROFIL JUMLAH NEOVASKULARISASI LUKA MENCIT HIPERGLIKEMIK YANG DIBERIKAN GEL EKSTRAK BUAH OKRA (Abelmoschus esculentus L.) - Chandra, Pra Panca Bayu; Lisnawati, Nia; Susanti, Yanthy (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
This study aimed to examine the gel activity of okra fruit extract (Abelmoschus esculentus L.) in mice with hyperglycemic conditions based on histopathological indicator parameters, namely the amount of neovascularization. Mus musculus strain male mice were hyperglycemic with STZ at a dose of 0.06 mg/gBW. Mice were divided into 8 groups (n=6). Group 1 (Non-DM Control), Group 2 (DM Control), Groups 3 to 8 (Test). The dose of glibenclamide was 5 mg/KgBW, the dose of okra fruit extract was 400 mg/KgBW and the dose of CMC Na was 5 mL/KgBW. Therapy was given once a day (oral and topical) for 15 days of therapy which was seen on days 0, 5, 11 and 15. The results of the study showed an increase in the number of neovascularizations on the 15th day of therapy in the test group compared to the control group. Administration of a combination of topical okra fruit extract gel with okra fruit extract orally for 15 days of therapy was able to increase the amount of neovascularization compared to administration without the combination or only orally. Administration of a combination of topical gel and oral okra fruit extract accelerated the wound healing process in hyperglycemic mice compared to non-combination administration. Management of fasting blood glucose levels has an effect on the success of the diabetic wound healing process.